Pemetaan Manajemen Rantai Pasok Kerupuk Udang di Kawasan Sungsang II Kabupaten Banyuasin - Janna, Miftahul; Adriani, Dessy; Bidarti, Agustina (Agriculture Faculty of Flores University, 2024)
Sungsang II villages are the main shrimp-producing areas located in the waters of the Musi River Estuary and South Bangka, South Sumatra Province. Shrimp are processed into various products, and crackers are the superior product. It's just that as a superior local product, until now there has been no research regarding the supply chain for shrimp crackers. This research aimed to map the supply chain management of processed shrimp cracker products in Sungsang II Villages. The research was carried out using a survey method. Thirty participants made up the entire sample, and the sampling procedure employed was multistage sampling. Data analysis uses mathematical, tabulated, and descriptive methods. The research results show that shrimp cracker processing in the Sungsang area is a household-scale industry. The raw material for shrimp comes from breech waters, and the process of making crackers is traditionally done using human labor; drying still uses sunlight; and packaging is done simply with plastic. The price of shrimp raw materials ranges from IDR 15,000 to IDR 25,000 per kg, and processors can process 20 to 30 kg of shrimp raw materials per day. The selling price for shrimp crackers from retailers to consumers is IDR 50,000 per kg. The shrimp cracker supply chain involves fishermen as suppliers of shrimp raw materials, craftsmen who process shrimp into crackers, collecting traders, retailers, and consumers.